Study of bioactive proteins in the roots and root exudates of model plants - De-la-Peña, Clelia, author; Vivanco, Jorge M., advisor (Colorado State University. Libraries, 2007)
The plant root system serves many roles, including anchorage and uptake of nutrients and water. The ability of roots to release a wide range of organic and inorganic compounds into the rhizosphere to communicate with roots of other plants and other organisms has been the focus of recent studies. Among the compounds released into the rhizosphere, proteins comprise an important amount of energy secreted by roots but have not been studied in detail. In the present study, I conducted a proteomic and enzymatic analysis of Arabidopsis thaliana root exudation across a developmental gradient to track the changes that occur in the root-secreted proteins at different plant developmental stages. Further, I found that the secretion of proteins (including pathogenesis-related [PR] proteins, myrosinases, and enzymes related to protein refolding) was qualitatively and quantitatively related to the growth stage of the plant. For instance, the intensity and activity of PR proteins such as chitinases were higher at peak flowering times than at any other time during Arabidopsis development. I also studied the root secretion of proteins by two model plants (Medicago sativa and A. thaliana) during their interaction with the symbiont of one of these specks (Sinorhizobium meliloti) and with an opportunistic pathogen of A. thaliana (Pseudomonas syringae pv. tomato DC3000). I found that the early interactions between M.sativa and S. meliloti induced exudation of enzymes such as acid chitinases, thaumatin proteins, PR10 and PR1 proteins. However, these proteins were not induced when M. saliva was inoculated with P. syringae DC3000. In addition, I found that P. syringae DC3000 could differentially induce the secretion of proteins related to defense in A. thaliana, whereas S. meliloti did not provoke the same response. The final study of my dissertation focused on the activity of ribosome-inactivating proteins (RIPS, PC 3.2.2.22) in Arabidopsis thaliana. Based on amino acid sequencing, it was determined that the purified RIP had homology to the mature form of a pectin methylesterase (PME, At1g11580); this purified protein showed PME activity. Further the A. thaliana full-length and mature PMF forms were cloned into the expression vector PQE30 and both constructs were expressed in Escherichia coli.
Keywords: bioactive proteins; plant-microbe interaction; root exudates; roots; horticulture; plant sciences